The Effectiveness of Whatsapp as An Online English Teaching Media at MTsN Kota Pasuruan : Teachers Perspectives - Nurul Faizah; Umroh Umroh; Rakhmawati Rakhmawati (Edulitics (Education, Literature, and Linguistics) Journal, 2021)
The COVID-19 pandemic has made many changes in the learning process system. With technology, Whatsapp has become one of the media that is widely used. This study investigates the effectiveness, problems, and solutions of WhatsApp as a virtual English learning media. This study uses a qualitative descriptive method with questionnaires and interviews as instruments. The results of the study show that Whatsapp is an effective, useful, and helpful media in learning English for students at MTsN Pasuruan. Teachers can also apply 4 skills in English Teaching with the help of the Whatsapp features. The results of this study proved that Whatsapp might be the best solution for distance learning English media. Keywords : Whatsapp, Online Learning, English Language Teaching